Impella support for cardiogenic shock and high-risk percutaneous coronary intervention: A single-center experience - Mariana Brandão (Elsevier, 2021)
Introduction and Objectives: The use of mechanical circulatory support is increasing in cases of cardiogenic shock (CS) and high-risk percutaneous coronary intervention (HR-PCI). The Impella® is a percutaneous ventricular assist device that unloads the left ventricle by ejecting blood to the ascending aorta. We report our center's experience with the use of the Impella® device in these two clinical settings. Methods: We performed a single-center retrospective study including all consecutive patients implanted with the Impella® between 2007 and 2019 for CS treatment or prophylactic support of HR-PCI. Data on clinical and safety endpoints were collected and analyzed. Results: Twenty-two patients were included: 12 were treated for CS and 10 underwent an HR-PCI procedure. In the CS-treated population, the main cause of CS was acute myocardial infarction (five patients); hemolysis was the most frequent device-related complication (63.7%). In-hospital, cumulative 30-day and one-year mortality were 58.3%, 66.6% and 83.3%, respectively. In the HR-PCI group, all patients had multivessel disease (mean baseline SYNTAX I score: 44.1±13.7). In-hospital, 30-day and one-year mortality were 10.0%, 10.0% and 20.0%, respectively. There were no device- or procedure-related deaths in either group. Conclusion: The short- and long-term results of Impella®-supported HR-PCI were comparable to those in the literature. In the CS group, in-hospital and short-term outcomes were poor, with high mortality and non-negligible complication rates. Resumo: Introdução e objetivos: O uso de suporte mecânico no choque cardiogénico (CS) e intervenção coronária percutânea de alto risco (HR-PCI) tem aumentado. O Impella® é um sistema de suporte ventricular percutâneo que ejeta sangue do ventrículo esquerdo para a aorta ascendente. Reportamos a experiência do nosso centro com o Impella® nestes dois cenários clínicos. Métodos: Estudo retrospetivo unicêntrico incluindo todos os doentes consecutivos submetidos a implantação de Impella® entre 2007 e 2019, para tratamento de CS ou suporte profilático para HR-PCI. Dados sobre endpoints clínicos e de segurança foram analisados. Resultados: Foram incluídos 22 doentes: 12 tratados por CS e 10 submetidos a HR-PCI. Na população de CS, a principal causa de choque foi o enfarte agudo do miocárdio (5 doentes); a hemólise foi a complicação relacionada com o dispositivo mais frequente (63,7%); a mortalidade intra-hospitalar, a 30 dias e um ano, foi, respetivamente, 58,3%, 66,6% e 83,3%. No grupo da HR-PCI, todos os doentes apresentavam doença multivaso (SYNTAX I score médio: 44,1±13,7); a mortalidade intra-hospitalar, a 30 dias e um ano, foi, respetivamente, 10,0%, 10,0% e 20,0%. Não houve mortes relacionadas com o dispositivo ou procedimento em ambos os grupos. Conclusão: Os resultados em curto e longo prazo da HR-PCI protegida por Impella® foram comparáveis aos da literatura disponível. No grupo de CS, os resultados intra-hospitalares e em curto prazo foram desanimadores, com elevada mortalidade e taxas de complicações apreciáveis.